The Great Discrepancy: Political Action, Sustainable Development and Ecological Communication - Konold, Dieter (2021)
The term ‘sustainable development’ was coined to denote a political goal some 40 years ago; debates about sustainability date back considerably further. These debates reflect the growing awareness of the destructive effects of human activities on the natural foundations of life. Numerous initiatives have been launched to trigger a turnaround, with the 2030 Agenda and the SDGs being the latest attempt. However, substantial progress has been rather limited thus far. This discrepancy is the subject of the article. Starting from a historical overview of sustainability politics, the argument develops in three steps. First, it is shown that conventional conceptions to promote environmental change fall short in depicting the broader societal context. To provide a comprehensive picture of the challenges related to transformation processes, a theory of the functional differentiation of societies is presented in a second step. A systems theory perspective offers a convincing theoretical explication of the problem. Third, this approach is scrutinized with regard to the political system and the politics of sustainability. The key finding is that the specific functional logics of the different social subsystems must be taken into account when analysing sustainable development and the discrepancy between the aims and ambitions of (global) environmental policy and the visible consequences. On the one hand, the functional differentiation of modern society guarantees its high degree of effectiveness and flexibility. On the other hand, implementing fundamental change, such as a transition towards sustainability, is not simply a question of strategy or of political willingness and steering. Rather, there is a need for more elaborate explanatory instruments. As a result, we argue for a linking of theories of sustainable development and advanced social theory.